Preserving - Steel, Susannah; Wright, Amanda (London ; New York : DK, 2013)
Have you always wanted to learn how to preserve your own jams, preserves, and chutneys, but don't know how to get started?More than 70 step-by-step recipes, taking you from complete beginner to being able to freeze, bottle, and pickle with confidence. Mix crunchy pickles, store luscious fruits in alcohol, and simmer spicy chutneys; build on your skills by boiling jams bursting with fruit and bottling vitamin-rich cordials; and show off by stirring fresh fruit curds to smooth perfection, curing fish and meat, and fermenting your own delicious wines. Packed with advice, reminders, and help when things go wrong, Get Started: Preserving will soon have you filling your pantry with delectable preserves.--
Start Simple : Frozen fresh fruit -- Frozen vegetables and herbs -- Vegetables in oil -- Bottled fruits in alcohol -- Simple salt preserves -- Pickles and freezer pickles -- Chutney and relish --- Build on it : Fruit cheese and fruit butter -- Jams and conserves -- Jelly -- Syrups and cordials -- Bottled fruits in syrup -- Dry fruit and vegetables --- Take it further : Marmalade -- Fruit curd -- Butter and soft cheese -- Alchoholic drinks -- Cured fish -- Cured and potted meat.
Includes index.
Keywords: Canning and preserving; Food -- Preservation; Canning and preserving; Food -- Preservation